Energy harvesting and information processing in two‐way multiplicative relay networks. Issue 9 (4th April 2016) - Shah, S.T.; Choi, K.W.; Hasan, S.F.; Chung, M.Y.
Abstract : An energy harvesting (EH) and information processing network based on two‐way multiplicative relay is proposed. In the proposed scheme, two nodes communicate with each other via an energy constrained multiplicative relay node. The relay node uses power splitting‐based relaying protocol for EH and information processing. The numerical results show that the proposed scheme outperforms the legacy amplify‐and‐forward EH relaying technique.